Examination of Nursing Students’ Status’ on Individualized Care - Seçil Gülhan Güner; Özlem Ovayolu; Nimet Ovayolu (Dokuz Eylül Üniversitesi Hemşirelik Fakültesi Elektronik Dergisi, 2020)
Background: Today, individualized care comes to the forefront in the education of nursing profession. Objectives: This study, at the a Faculty of Health Sciences in Turkey which were continuing his undergraduate studies which nursing department students ' status’ regarding individualized care in order to examine the was performed. Methods: The sample of this descriptive and cross-sectional study consisted of 414 nursing students in the second, third and fourth class of 2018-2019 academic year who were educated in the Nursing Department of the related Faculty, who had at least one year of nursing education and had clinical practice experience. The data of the study was collected with the Descriptive Information Form and the Individualized Care Scale Nurse version. Frequency, mean, percentage, Mann Whitney U and Kruskal Wallis were used to evaluate the data. Results: Students stated that 35.7% of the students thought that individualized care was given to the patient in the clinic, 74.6% found individualized care to be beneficial and 73% faced obstacles while providing individualized care to the patient. The barriers faced with in individualized care giving was seen; communication problems (43%), lack of time (39.9%), lack of materials (36%) and excess workload (35.3%) was seen. The total score of nursing students supporting patient individuality was 3.60 ± 0.92 and the mean of individualizing patient care was 3.68 ± 0.95 determined. Conclusion: It was seen that the average score of nursing students in support of patient individuality and individualization of patient care was found to be moderate, most of them found individualized care beneficial and encountered obstacles in the caregiving process. Accordingly, it may be suggested that in nursing undergraduate education students should be educated, practiced and supported on the importance of individualized care during.